2006
DOI: 10.1007/s11483-006-9015-2
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Compositional Factors against the Thermal Oxidative Deterioration of Novel Food Emulsions

Abstract: This work attempts to determine any relationship between certain endogenous parameters and the oxidative deterioration of protein-stabilized oil-in-water emulsions. The contribution of compositional factors (e.g., type and amount of emulsifier, fat phase, etc.) is further elucidated. Among 10% cottonseed o/w emulsions prepared by 1% emulsifier (Tween, sodium caseinate, or whey protein), lipid autoxidation (at 40°C) was much faster in the Tween emulsion than in the protein ones, with whey protein presenting a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 33 publications
3
49
1
Order By: Relevance
“…Such an influence of emulsifier composition on oxidation has been recently reported and discussed by Kiokias et al 9 The results of this study indicated that the formation of primary oxidation products in emulsions is strongly temperature-dependent and the quantification of the reaction rate's reliance with temperature could help to monitor the oxidative alterations. On the other hand, the effect of pH is associated with the emulsifier used, and is more pronounced in Tween-stabilized emulsions.…”
Section: Effect Of Ph On the Oxidative Stability Of O/w Emulsionssupporting
confidence: 76%
See 2 more Smart Citations
“…Such an influence of emulsifier composition on oxidation has been recently reported and discussed by Kiokias et al 9 The results of this study indicated that the formation of primary oxidation products in emulsions is strongly temperature-dependent and the quantification of the reaction rate's reliance with temperature could help to monitor the oxidative alterations. On the other hand, the effect of pH is associated with the emulsifier used, and is more pronounced in Tween-stabilized emulsions.…”
Section: Effect Of Ph On the Oxidative Stability Of O/w Emulsionssupporting
confidence: 76%
“…A mixture of Tween/Na-CAS 1:1 was used and an emulsion with higher oil concentration was prepared, which is closer to the formulation of innovative real products. 9 From this point of view, this certain emulsion system was selected as appropriate to further examine any effect of pH. The water bath temperature was adjusted to 60°C to accelerate the oxidation experiment.…”
Section: Effect Of Temperature On the Oxidative Stability Of O/w Emulmentioning
confidence: 99%
See 1 more Smart Citation
“…Richards, Golding, Wijesundera, and Lundin (2011) reported that the combination of SC with non-ionic small molecular emulsifiers showed greater inhibitory effect on lipid oxidation of o/w emulsions as compared to using it individually or in combination with ionic small molecular emulsifiers. Kiokias, Dimakou, Tsaprouni, and Oreopoulou (2006) could also improve the oxidative deterioration of linolenic acid in o/w emulsions by using a twocomponent stabilizer mixtures composed of polysorbates and globular proteins. In these systems, by increasing the proportion of polysorbates, protein displacement is simultaneously enhanced leading to the weakening of the thickness and functionality of the protein interfacial layer.…”
Section: Astaxanthin Loss and Chemical Stabilitymentioning
confidence: 99%
“…2 Lipid oxidation in food results in off-flavors and toxic products due to the peroxidation of unsaturated fatty acids. 3,4 Therefore, evaluating of lipid oxidation in emulsions is important to control the quality and safety of food.…”
Section: Introductionmentioning
confidence: 99%